Brazilian educational diplomacy: PEC-G and PEC-PG as foreign policy tools - Ferreira, Gabriela Gomes Coelho (2019)
Can developing countries influence the transnational arena using science and education as foreign policy tools? Soft power is usually related to developed countries as consequence of military and economic power. However, taking in account its owns constraints, major developing countries are designing strategies adapted to the new transnational arena modified by technological transformations. Those strategies include scientific and educational agreements towards an exchange of knowledge and shaping public opinion: science, education and innovation diplomacy. To shed light on the central question presented above, I will use as a case study the Brazilian international scholarship program, addressing other issues. Do Brazilian scholarships influence these students\' perception towards the country\'s projection in the international arena? What are the determinants of their perception? Do these students become elites who can influence Brazilian international relations in the future? Thereby, I aim to analyse the role of the international scholarships funded by the Brazilian government to assess the factors that contribute to the success or not of the Brazilian Educational and Foreign Policy. Using a survey with different groups of international students and researchers, I will use statistical analysis to compare their perception of Brazil, indicating the effect of some determinants as field of study, country of residence and the Brazilian region where they pursued their degrees or realized their researches. Also, the survey allows enlighten soft power indicators according to the literature.